Wavelength sensitivity of the speckle patterns produced by an integrating sphere. (29th July 2021) - Facchin, Morgan; Dholakia, Kishan; Bruce, Graham D
Abstract: Speckle metrology is a powerful tool in the measurement of wavelength and spectra. Recently, speckle produced by multiple reflections inside an integrating sphere has been proposed and showed high performance. However, to our knowledge, a complete characterisation of speckle sensitivity to wavelength in that geometry has not been performed to date. In this work, we derive a general model predicting the variation in a speckle pattern as a result of a generic transformation. Applying this to a shift in the incident wavelength, we show that the speckle sensitivity is mainly governed by the radius and surface reflectivity of the sphere. We show that integrating spheres offer sensitivity four orders of magnitude above that of multimode fibres of a similar size, and discuss analogies with the transmission profile of a Fabry–Pérot interferometer.